The conduct of hostilities under the law of international armed conflict - Dinshṭeyn, Yoram (Cambridge Univ. Press, 2010)
1. The general framework; 2. Lawful combatancy; 3. Prohibited weapons; 4. Lawful targets of attack; 5. Protection from attack of civilians and civilian objects; 6. Measures of special protection from attack; 7. Protection of the environment; 8. Specific methods of warfare; 9. War crimes, orders, command responsibility and defences; General conclusions